Inhibition of eukaryotic translation initiation factor 5A (eIF5A) hypusination impairs melanoma growth - Jasiulionis, Miriam G.; Luchessi, Augusto D.; Moreira, Andreia G.; Souza, Pedro P. C.; Suenaga, Ana P. M.; Correa, Mariangela; Costa, Carlos A. S. [UNESP]; Curi, Rui; Costa-Neto, Claudio M. (Wiley, 2007)
The eukaryotic translation initiation factor 5A (eIF5A) undergoes a specific post-translational modification called hypusination. This modification is required for the functionality of this protein. The compound N1-guanyl-1,7-diaminoheptane (GC7) is a potent and selective inhibitor of deoxyhypusine synthase, which catalyses the first step of eIF5A hypusination process. In the present study, the effects of GC7 on cell death were investigated using two cell lines: melan-a murine melanocytes and Tm5 marine melanoma. In vitro treatment with GC7 increased by 3-fold the number of cells presenting DNA fragmentation in Tm5 cells. Exposure to GC7 also decreased viability to both cell lines. This study also describes, for the first time, the in vivo antitumour effect of GC7, as indicated by impaired melanoma growth in C57BL/6 mice. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: Cell proliferation; Cytotoxicity; eIF-5A; eIF5A; GC7; Hypusine; Melanoma; Tumour growth; enzyme inhibitor; initiation factor 5A; n1 guanyl 1,7 diaminoheptane; unclassified drug; animal cell; antineoplastic activity; cancer growth; cancer inhibition; catalysis; cell death; cell viability; controlled study; hypusination; melanoma; melanoma cell; mouse; nonhuman; priority journal; protein function; protein processing; Animals; Cell Line, Tumor; Cell Survival; DNA Fragmentation; Female; Guanine; Mice; Mice, Inbred C57BL; Molecular Structure; Peptide Initiation Factors; Protein Processing, Post-Translational; RNA-Binding Proteins; Eukaryota; Murinae; Mus